DETERMINING FACTORS OF MEDIATOR'S SUCCESS IN METRO RELIGIOUS COURTS - Muhammad Rendi (Jurnal Multidisiplin Sahombu, 2022)
Mediation is an alternative dispute resolution that can be used by court parties. This institution provides an opportunity for the parties to play a role in resolving disputes with the assistance of a third party, namely a mediator. The parties to the dispute or litigation in court must of course go through a mediation process first. The mediation process in resolving cases is forced or compulsory. Therefore, the parties to the litigation have no choice but to comply. The religious court as one of the implementers of judicial power has practiced mediation in the case settlement process. Theoretically, dispute resolution through mediation in the Religious Courts brings a number of advantages, Among other things, cases can be resolved quickly and at low cost and reduce congestion and build-up of cases (court congestion) in the Court. What is the success rate of mediators at the Metro Religious Courts and what are the determinants of the success of mediators at the Metro Religious Courts? This study aims to determine the success rate of mediation and the determinants of the success of the mediator at the Metro Religious Court. This type of research is field research, namely this research was conducted at the Metro Religious Court. Sources of data used in this study are primary data sources, namely sources obtained directly from Mediator Judges who carry out mediation efforts at the Metro Religious Courts and secondary data sources, namely data sources obtained from records and books related to the problems studied. The data collection technique in this research is the interview and documentation method. Then the data analysis used is descriptive qualitative analysis. Based on the research that has been done, it can be concluded that the determining factor for the success of the mediator at the Metro Religious Court is the level of public awareness in undergoing the mediation process is very low. It is based on psychological, good faith, and moral and spiritual parties. Supporting facilities and facilities at the Metro Religious Courts are not yet ideal.